Evaluation of Mesocyclops annulatus (Copepoda: Cyclopoidea) as a control agent of Aedes aegypti (Diptera: Culicidae) in Argentina - Martí, Gerardo Aníbal (2004)
We evaluated the potential of Mesocyclops annulatus as a control agent of Aedes aegypti in La Plata city (Argentina). Mosquito larval survivorship due to predation by these copepods was estimated at weekly intervals during the oviposition period of A. aegypti. Mean weekly A. aegypti larval survivorship in cylindrical plastic containers (12 cm height and 11 cm diameter) with copepods was significantly lower than in control containers. Furthermore, weekly larval survival was negatively correlated with M. annulatus adult density, and approximately 23 adult copepods/container would be a threshold density over which the weekly mosquito larval survivorship approached zero. The copepods were able to persist in all containers during approximately 100 days (in three of them until the end of the experiment: 155 days) without the resource represented by A. aegypti larvae. The predation and persistence observed suggest that M. annulatus is a potential control agent to be considered in biological control programs.